The Influence of Market To Book Value, Growth Opportunities, Financial Distress and Interest Coverage Ratio on Hedging Decisions in Indonesian Manufacturing Companies in 2014-2018: Pengaruh Market To Book Value, Growth Opportunities, Kesulitan Keuangan Dan Interest Coverage Ratio Terhadap Keputusan Hedging Pada Perusahaan Manufaktur Indonesia Tahun 2014-2018 - Mitha Rachma Diana; Sriyono Sriyono (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to determine the effect of Market to Book Value, Growth Opportunities, Financial Distress and Interest Coverage Ratio on Hedging Decisions in Indonesian Manufacturing Companies. This study uses a quantitative method and the object of this research is a population and a random sample (purposive sampling), namely 60 Indonesian manufacturing companies listed on the Indonesia Stock Exchange in 2014-2018. The type of data used in this study is secondary taken from the company's annual report for the 2014-2018 period. The data analysis technique uses logistic regression method using the Eviews 9 program. The results of this study indicate that simultaneously the variables of Market to Book Value, Growth Opportunities, Financial Difficulties and Interest Coverage Ratio have an influence on Hedging Decisions. Meanwhile, partially Growth Opportunities, Financial Distress and Interest Coverage Ratio have a significant effect on Hedging Decisions. Meanwhile, Market to Book Value has no significant effect on Hedging Decisions.